2015
DOI: 10.1515/hsz-2015-0150
|View full text |Cite
|
Sign up to set email alerts
|

The assembly and disassembly of the AcrAB-TolC three-component multidrug efflux pump

Abstract: In Gram-negative bacteria, tripartite efflux pumps, like AcrAB-TolC from Escherichia coli, play a prominent role in the resistance against multiple antibiotics. Transport of the drugs across the outer membrane and its coupling to the electrochemical gradient is dependent on the presence of all three components. As the activity of the E. coli AcrAB-TolC efflux pump is dependent on both the concentration of substrates and the extent of the electrochemical gradient across the inner membrane, the dynamics of tripa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 9 publications
3
18
0
1
Order By: Relevance
“…tolC is well known to be involved in the efflux of a great many substances because it is linked to a variety of inner-membrane efflux transporters [69,72,[120][121][122]. In this case the uptake of the majority of the palette was, as expected, greater than in the wild type in the tolC deletion strain.…”
Section: The Profiles Observed With Gene Knockouts Discriminate Influsupporting
confidence: 55%
“…tolC is well known to be involved in the efflux of a great many substances because it is linked to a variety of inner-membrane efflux transporters [69,72,[120][121][122]. In this case the uptake of the majority of the palette was, as expected, greater than in the wild type in the tolC deletion strain.…”
Section: The Profiles Observed With Gene Knockouts Discriminate Influsupporting
confidence: 55%
“…165 Considering these findings and the observation from Kralj et al that in E. coli a rapidly spiking (∼1 Hz) PMF coincided with the efflux of the potential AcrB substrate tetramethyl rhodamine methylester, 166 we and others have suggested that the AcrAB-TolC MDEP operates in a discontinuous fashion. 167 Some uncertainty still remains concerning the tripartite setup, since clear cross-linking between AcrB and TolC has been observed. 168 Moreover, the expression of genetic fusions between acrA and acrB in an E. coli acrAB strain resulted in drug resistance.…”
Section: Structural and Functional Dynamics Of The Acrab(z)-tolc Complexmentioning
confidence: 99%
“…Due to the limited resolution, these studies were unable to identify the detailed interaction interfaces between the components. Moreover, the mechanism of pump assembly and channel opening is presently unclear (Müller and Pos, 2015; Zgurskaya et al, 2015) and requires detailed structural information of the pump in the different conformational states that accompany drug translocation. In this study, we report the near-atomic resolution cryoEM structures of the AcrAB-TolC pump captured in both resting and drug transport states.…”
Section: Introductionmentioning
confidence: 99%